2011
DOI: 10.1094/cchem-05-10-0077
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antinutritional Factors of Field Peas (Pisum sativum), Chickpeas (Cicer arietinum), and Faba Beans (Vicia faba) as Affected by Extrusion Preconditioning and Drying Temperatures

Abstract: Legumes are valuable plant sources of protein and energy and extrusion is one of the most common processing methods for manufacturing both human food and animal feeds. In the present study, three different legumes (field peas, chickpeas, and faba beans) were ground and processed in a pilot‐scale extrusion line. Various preconditioning and dryer temperatures were applied to each legume separately that reflected or differed from standard manufacturing conditions. Although literature exists regarding the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 42 publications
1
32
0
3
Order By: Relevance
“…For this case, the preconditioner, outlet and dryer temperature during the process have played important roles, since they have varied from 70.5 to 100 °C, 108 to 116 °C, and 89 to 147 °C respectively. An important insight obtained by this study was that high temperatures were needed only for the preconditioner treatment of chickpeas, while for faba beans the process needed the highest level of temperature (Adamidou and others ). These results suggest that TIs are more heat‐labile in the case of chickpeas.…”
Section: Physical Processesmentioning
confidence: 87%
See 1 more Smart Citation
“…For this case, the preconditioner, outlet and dryer temperature during the process have played important roles, since they have varied from 70.5 to 100 °C, 108 to 116 °C, and 89 to 147 °C respectively. An important insight obtained by this study was that high temperatures were needed only for the preconditioner treatment of chickpeas, while for faba beans the process needed the highest level of temperature (Adamidou and others ). These results suggest that TIs are more heat‐labile in the case of chickpeas.…”
Section: Physical Processesmentioning
confidence: 87%
“…In the case of soybeans, it also inactivates lipooxygenase, an enzyme that catalyzes deoxygenation of some polyunsaturated fatty acids. The oxidized fatty acids are known to promote inflammation and hypersensitivity reactions and generate undesirable off‐odors associated with flavor reversion (Adamidou and others ; Žilić and others ). Functional properties of legumes have also been studied in parallel with TIs inactivation during extrusion.…”
Section: Physical Processesmentioning
confidence: 99%
“…Avanza et al (2013) reported increased protein content of cowpea subjected to soaking, cooking, and autoclaving and that the highest protein content for each process was associated with the shortest processing time. Adamidou et al (2011) reported both an increase and a decrease in protein content of chickpea, faba beans, and peas during extrusion processing. Simons et al (2015) reported no change in protein of extruded navy, black, and pinto beans.…”
Section: Protein Content and Composition Of Pulse Cropsmentioning
confidence: 99%
“…The ash content of pinto beans that were boiled, cooked, or roasted was higher than the ash content of raw pinto beans (Audu and Aremu 2011). Small but insignificant reductions in ash content during extrusion of peas, faba beans, and chickpeas were observed (Adamidou et al 2011). The ash contents of faba beans and yellow peas decreased upon germination, whereas small increases in ash were observed in lentils (Morad et al 1980).…”
Section: Mineral Composition and Content Of Pulse Cropsmentioning
confidence: 99%
“…przez stosowanie zabiegów uszlachetniających (obłuszczanie, ekstruzja), jednak wiążą się one z kosztami (Adamidou i in., 2011;Hejdysz i in., 2016;Milczarek i Osek, 2016;Usayran i in., 2014). Efektem prac selekcyjnych jest stworzenie niskotaninowych odmian bobiku.…”
Section: Wstępunclassified